2018
DOI: 10.3390/jcm7030043
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Success Rate of Percutaneous Nephrolithotomy in Paediatric Patients

Abstract: In this study, we aimed to determine factors affecting the success rate of percutaneous nephrolithotomy (PNL) in children. The series consisted of 41 consecutive children operated on by the same surgical team for renal calculi with PNL between June 2002 and May 2015 in our institution. A single calyx or pelvic stone was described as simple, while calculi located in more than one location (calyx and pelvis or more than one calices) or staghorn stones were described as complex. The procedure was deemed successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…By increasing surgeon experience and technological development of tools using in PNL surgery increase the success of the surgery and decrease the complication rate. However, it is known that the success of PNL is also affected by some other influencers such as hydronephrosis, stone location, and as well as Hounsfield unit (HU) [3]. Gucuk et al [4] showed that the higher HU values increase the stone-free rate and HU is an independent predictive factor affecting the success of PNL.…”
mentioning
confidence: 99%
“…By increasing surgeon experience and technological development of tools using in PNL surgery increase the success of the surgery and decrease the complication rate. However, it is known that the success of PNL is also affected by some other influencers such as hydronephrosis, stone location, and as well as Hounsfield unit (HU) [3]. Gucuk et al [4] showed that the higher HU values increase the stone-free rate and HU is an independent predictive factor affecting the success of PNL.…”
mentioning
confidence: 99%